Intensification of toxic chlorophenolic compounds degradation over efficient microwave-dried silica-doped tetragonal zirconia nanocatalysts - Hassan, N. S.; Jalil, A. A.; Hussain, I.; Fauzi, A. A.; Azami, M. S.; Saravanan, R.; Hairom, N. H. H. (Elsevier, 2021)
The work aims to evaluate the efficient microwave (MW) drying method of silica-doped tetragonal zirconia nanocatalysts (SZN-M) for intensification of the degradation of toxic chlorophenolic compounds. The catalyst dried under a conventional oven (SZN-O) was also conducted for comparison. The MW drying time was reduced six times and three times less energy was used than the conventional oven drying. The catalysts were characterized by Fourier-transform infrared, X-ray diffraction, electron spin resonance, nitrogen adsorption-desorption analyses, zeta potential, ultraviolet–visible diffuse reflectance spectroscopy and photoluminescence analyses. Compared with SZN-O, the SZN-M possessed a higher number of Si-O-Zr bonds that led to a greater amount of oxygen vacancies, metal defect sites, larger pore size as well as surface area, and hence displayed excellent performance toward the degradation of toxic 2-chlorophenol, 2-CP (92%), while only 67% for the former. The SZN-M achieved to reduce the total organic carbon and biological oxygen demand up to 88% and 89%, respectively, while for SZN-O, the reduction was up to 82% and 84%. The catalysts still remained active after five cycles and are highly capable of degrading various chlorophenolic compounds that could be very beneficial for the wastewater treatment.